2016
DOI: 10.3389/fpls.2016.01279
|View full text |Cite
|
Sign up to set email alerts
|

The SOD Gene Family in Tomato: Identification, Phylogenetic Relationships, and Expression Patterns

Abstract: Superoxide dismutases (SODs) are critical antioxidant enzymes that protect organisms from reactive oxygen species (ROS) caused by adverse conditions, and have been widely found in the cytoplasm, chloroplasts, and mitochondria of eukaryotic and prokaryotic cells. Tomato (Solanum lycopersicum L.) is an important economic crop and is cultivated worldwide. However, abiotic and biotic stresses severely hinder growth and development of the plant, which affects the production and quality of the crop. To reveal the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
122
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 80 publications
20
122
1
1
Order By: Relevance
“…The results revealed that four and six of soybean SOD genes were significantly induced under alkaline and salt stresses, respectively. Similarly, studies have reported that SOD genes played positive roles in other plants (Feng et al, 2016). Whereas, almost all the expression levels of soybean SOD genes displayed no significant change under cold stress, except for a slightly up-regulation (|Log 2 fold change| > 1) of GmFSD2.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The results revealed that four and six of soybean SOD genes were significantly induced under alkaline and salt stresses, respectively. Similarly, studies have reported that SOD genes played positive roles in other plants (Feng et al, 2016). Whereas, almost all the expression levels of soybean SOD genes displayed no significant change under cold stress, except for a slightly up-regulation (|Log 2 fold change| > 1) of GmFSD2.…”
Section: Discussionmentioning
confidence: 68%
“…Antioxidant enzymes SOD play significantly roles in plant response to abiotic stresses by reducing the molecular oxygen and hydrogen peroxide in plant cells. The plant SOD family genes have been identified and characterized in some species at the genome-wide level (Feng et al, 2016;Verma, Lakhanpal & Singh, 2019). However, the roles of soybean SOD family genes in regulating various abiotic stresses, especially alkaline stress, are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such conditions, plants attempt to decrease photosystem II activity by activating the Mehler peroxidase reaction (reviewed in [70]), which results in an increase in superoxide radicals. Increased oxygen radicals stimulate SOD production [71,72], and APX and catalase expression activity during tomato fruit ripening [73]. Increased level of APX expression was also observed in Lactuca sativa L. cv Romaine leaves when Mehler reaction was initiated by potassium cyanide (KCN)mediated inhibition of the electron transport chain [74].…”
Section: Photosynthetic/respiratory Processesmentioning
confidence: 99%
“…High-throughput genomic and transcriptomic sequencing techniques are powerful tools that have been used to gain comprehensive genomic information of the novelty and plasticity underlying the adaptation response of plants under salt stress. Many studies have focused on the transcriptional reprogramming of the related biological processes [ 11 13 ]. However, because most biological functions are carried out by proteins, and posttranscriptional regulation and posttranslational modifications can influence a system, quantitation of the proteins in a system is mandatory to understand the biological process and functions involved [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%